Confidence And Anxiety In Students Who Are Preparing To Write A Thesis - Rizka Fibria Nugrahani; Tsamrotul Fuadi (IJIP : Indonesian Journal of Islamic Psychology, 2023)
Anxiety is a common experience, especially among students who are about to face their thesis. This feeling of anxiety is often influenced by their level of self-confidence. For instance, sixth semester students who are preparing to write their thesis often view it as a daunting task, which leads to anxiety. This study aimed to investigate the relationship between self-confidence and anxiety among psychology students in their sixth semester, who are about to embark on their thesis writing journey. The hypothesis proposed was that there is a negative correlation between self-confidence and anxiety. The study employed a quantitative method that utilizes numerical data. The results obtained from the study showed a significant negative correlation between self-confidence and anxiety, with a correlation coefficient of r = -0.326, p = 0.021 (less than 0.05). This means that an increase in self-confidence is associated with a decrease in anxiety among sixth-semester students who are about to write their thesis. Therefore, the research hypothesis was accepted.